TYPES OF ESSENTIAL ESL TEACHING METHODS IN PRE-SERVICE EDUCATION - Ikromova Muazzam Dilmurod kizi (Western European Studies, 2024)
The present study contributes to the field of English as a Second Language education by examining the effectiveness of different teaching methods, including interactive techniques, technology integration, and culturally responsive teaching strategies. By relying on a mixed methods research methodology that relied on a triangulation of classroom observations, literature review, and ESL teacher surveys, this study identified several strategies that may have a positive impact on language learning. In particular, the results suggested that interactive activities improve student engagement and promote hands-on practical language application, technology use in classrooms ensures inclusivity and supports the diverse needs of learners via multimedia supports, and culturally responsive teaching that integrates students’ social and cultural backgrounds into the learning process increases relevance and motivation. The current paper also addresses the implications of these findings for ESL practitioners and lists potential avenues for further studies that could help advance ESL pedagogy in the future. The results of the study serve as a call to ESL teachers to employ these methods in their classrooms and modify them to fit their specific teaching and learning context to promote the effectiveness of this type of language instruction and inclusivity within classrooms.
Keywords: ESL Teaching Methods; learning process; English